2012
DOI: 10.1115/1.4006336
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Investigation of Flow Field and Downstream Surface Temperatures of Cylindrical and Diffuser Shaped Film Cooling Holes1

Abstract: An experimental and numerical study of the flow field and the downstream film cooling performance of cylindrical and diffuser shaped cooling holes is presented. The measurements were conducted on a flat plate with a single cooling hole with coolant ejected from a plenum. The flow field was investigated by means of 3D-PIV as well as 3D-LDV measurements, the downstream film cooling effectiveness by means of infrared thermography. Cylindrical and diffuser holes without lateral inclination have been examined, vary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…Only one study was found to report measured flowfields for shaped holes with high-density ratio jet injection at elevated freestream turbulence intensity [12]. The present study builds upon those results by contrasting shaped hole performance at low and high freestream turbulence intensities at conditions not previously reported in literature.…”
Section: Previous Studiessupporting
confidence: 68%
“…Only one study was found to report measured flowfields for shaped holes with high-density ratio jet injection at elevated freestream turbulence intensity [12]. The present study builds upon those results by contrasting shaped hole performance at low and high freestream turbulence intensities at conditions not previously reported in literature.…”
Section: Previous Studiessupporting
confidence: 68%
“…Even if it is not reported in the results, this overlapping phenomena of the jets was found on all the measured row for both geometries (up to the fourth) with a progressive weakening of the phenomenon moving away from the swirler. Finally, looking to the lateral spots of the jets from the previous row (s = ±2.5), it is clear how the cores of the jets assume a stretched and elongated shape, far from the classical behaviour in the presence of an axial flow [20][21][22]. It is possible to speculate that such a strong deviation underline that any correlative approach to estimate cooling effectiveness based on formulations developed on fundamental test cases could be completely ineffective especially in the near dome region.…”
Section: Swirling Flow Characterizationmentioning
confidence: 95%
“…This paper, likewise in the efforts by Kampe et al [23], aims at the clarification of detailed velocity field associated with cooling holes using 3D-LDV and their characteristics in film effectiveness on the wall measured by IR camera. This paper especially deals with multiple cooling holes with two types of in-line configurations.…”
Section: Introductionmentioning
confidence: 97%
“…It was concluded that the main reason behind poorer film cooling performance at higher turbulent level is due to the enhancement of the mixing between the coolant and the mainstream air which lead to coolant temperature drop thus reducing its cooling capacity. Kampe et al [23] presented a complete study of diffuser shape film cooling holes covering both the thermal and the aerodynamics aspects. The thermal measurements have been made by IR camera while both PIV and LDV have been used in the aerodynamics measurements.…”
Section: Introductionmentioning
confidence: 99%